Preparation of Electrospun Porous Alumina Nanofibers for Origami‐Inspired Manufacturing. Issue 12 (14th December 2022) - Ni, Yu; Gupta, Ankur; Verma, Gulshan; Gupta, Sparsh; Weidler, Peter G.; Mager, Dario; Korvink, Jan G.; Islam, Monsur
Abstract : This work demonstrates origami‐inspired manufacturing of alumina nanofibers as described in the article number 2201183 by Jan G. Korvink, Monsur Islam, and co‐workers. Folding of an electrospun nanofiber sheet of a precursor materials followed by heat treatment results in the 3D origami structures of alumina nanofibers. The alumina nanofibers can be tuned to feature either porous or hollow morphology.